Hidden complexity in the ontogeny of sexual size dimorphism in male-larger beetles - Vendl, Tomáš; Šípek, Petr; Kouklík, Ondřej; Kratochvíl, Lukáš (Scientific reports, 2018)
Sexual size dimorphism (SSD) is widespread among animals, but its developmental mechanisms are not fully undestood. We investigated the proximate causes of SSD in three male-larger and one monomorphic scarab beetles using detailed monitoring of growth in individual instars. Apart from the finding that SSD in all three male-larger species started to develop already in the first larval instar, we generally found a high variability in SSD formation among the species as well as among instars. Overall, sexual differences in developmental time, average growth rate, as well as in the shape of the growth trajectory seem to be the mechanisms responsible for SSD ontogeny in scarab beetles. In the third instar, when the larvae attain most of their mass, the males had a similar or even lower instantaneous growth rate than females and SSD largely developed as a consequence of a longer period of rapid growth in males even in cases when the sexes did not differ in the total duration of this instar. Our results demonstrate that a detailed approach, examining not only the average growth rate and developmental time, but also the shape of the growth trajectory, is necessary to elucidate the complex development of SSD.
Keywords: Coleoptera; brouci; velikost těla; Sex Characteristics; Biological Evolution; Male; Larva; larva; Animals; biologická evoluce; mužské pohlaví; ženské pohlaví; Body Size; pohlavní dimorfismus; Female; zvířata